Evaluation of Physician and Nurse Dyad Training Procedures to Deliver a Palliative and End-of-Life Communication Intervention to Parents of Children with a Brain Tumor. (September 2015) - Hendricks-Ferguson, Verna L.; Kane, Javier R.; Pradhan, Kamnesh R.; Shih, Chie-Schin; Gauvain, Karen M.; Baker, Justin N.; Haase, Joan E.
When a child's prognosis is poor, physicians and nurses (MDs/RNs) often struggle with initiating discussions about palliative and end-of-life care (PC/EOL) early in the course of illness trajectory. We describe evaluation of training procedures used to prepare MD/RN dyads to deliver an intervention entitled:Com municationPl an:E arlyT hroughE nd of Life (COMPLETE) intervention. Our training was delivered to 5 pediatric neuro-oncologists and 8 pediatric nurses by a team of expert consultants (i.e., in medical ethics, communication, and PC/EOL) and parent advisors. Although half of the group received training in a 1-day program and half in a 2-day program, content for all participants included 4 modules: family assessment, goal-directed treatment planning, anticipatory guidance, and staff communication and follow-up. Evaluations included dichotomous ratings and qualitative comments on content, reflection, and skills practice for each module. Positive aspects of our training included parent advisers' insights, emphasis on hope and non-abandonment messages, written materials to facilitate PC/EOL communication, and an MD/RN dyad approach. Lessons learned and challenges related to our training procedures will be described. Overall, the MDs and RNs reported that our PC/EOL communication-training procedures were helpful and useful. Future investigators should carefully plan training procedures for PC/EOL communication interventions.